2013
DOI: 10.1590/s0031-10492013003200001
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for monitoring avian populations with point counts: a case study in southeastern Brazil

Abstract: In the northern hemisphere, bird counts have been fundamental in gathering data

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…We sampled each sampling unit for two days, and we sampled each sampling point four times (as if they had been sampled on four mornings). Studies performed in the Atlantic Forest using the point count method demonstrated that 3 to 5 days of sampling are sufficient to detect more than 90% of the species recorded in a sample area (Anjos 2007, Cavarzere et al 2013. Sampling began shortly after sunrise, when daytime birds start to vocalize, and ended 2.5 h after sampling at the first point, under favorable climatic conditions.…”
Section: Bird Samplingmentioning
confidence: 99%
“…We sampled each sampling unit for two days, and we sampled each sampling point four times (as if they had been sampled on four mornings). Studies performed in the Atlantic Forest using the point count method demonstrated that 3 to 5 days of sampling are sufficient to detect more than 90% of the species recorded in a sample area (Anjos 2007, Cavarzere et al 2013. Sampling began shortly after sunrise, when daytime birds start to vocalize, and ended 2.5 h after sampling at the first point, under favorable climatic conditions.…”
Section: Bird Samplingmentioning
confidence: 99%
“…We used the counting point sampling method to record species richness and number of individuals in each area (Volpato et al 2009). Two observers remained for 15 minutes at each point (Cavarzere et al 2013) and recorded birds sighted and heard within approximately 30 m. Samples were taken from October to December 2016, during the reproductive period of most bird species in southern Brazil (Belton 1994).…”
Section: Data Collectionmentioning
confidence: 99%